Total electron skin body irradiation in the course of Mycosis fungoides - Rubik, Agnieszka; Jarema, Alina; Rogowska, Danuta; Kubrak, Jadwiga; Boehlke, Marek; Lewocki, Mirosław; Marzęcki, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 1999)
Mycosis fungoides belongs to low malignant Hodgkin’s disease. In the majority of cases disease progresses slowly. Changes on the skin are superficial and non-specific. Medical survival after histological confirmation of disease lost 5-10 years. Photochemotherapy, superficial chemotherapy with alkilating agents and radiotherapy of the whole skin are presently used. Introduction of electron created new possibility of radiotherapy in that disease. In Radiotherapy Clinic of Pomeranian Medical Academy six fields irradiation described by Karzmark and modified by Page was used. 5 MeV electrons generated by accelerator Mevatron MD was utilised. The authors described two cases of mycosis fungoides which were irradiated in last two years.